PENGARUH PEMANFAATAN PECAHAN TERUMBU KARANG SEBAGAI PENGGANTI AGREGAT HALUS TERHADAP KUAT TEKAN BETON - Adika Kurniawan; Yuzuar Afrizal; Agustin Gunawan (Universitas Bengkulu, 2019)
Fractional reef has similarities with fine aggregate used as a substitute fine aggregate in theconcrete mix. This study aims to determine the optimal percentage of replacement fragments ofcoral reefs as a substitute for fine aggregate of compressive strength of concrete at 28 days.Test specimen using a slump of 0.6 fas 60-100 cube measuring 15 cm x 15 cm x 15 cm by 20samples. Variation replacement coral fragments used were 25%, 50%, 75% and 100% of theweight of the volume of fine aggregate. The results of the study of fine aggregate replacement with shards of coral reefs have increased the compressive strength of normal concrete. The percentage increase in the compressive strength of concrete for a variation of 3.024% P25replacement, replacement of variation of 6.61% P 50, P 75 variations replacement of 9.219 andvariations replacement P 100 at 1.220%.